Integrin-associated transcriptional characteristics of circulating tumor cells in breast cancer patients - Evgeniya Grigoryeva; Liubov Tashireva; Vladimir Alifanov; Olga Savelieva; Marina Zavyalova; Maxim Menyailo; Anna Khozyainova; Evgeny V. Denisov; Olga Bragina; Nataliya Popova; Nadezhda V. Cherdyntseva; Vladimir Perelmuter (PeerJ, 2024)
Background Integrins enable cell communication with the basal membrane and extracellular matrix, activating signaling pathways and facilitating intracellular changes. Integrins in circulating tumor cells (CTCs) play a significant role in apoptosis evasion and anchor-independent survival. However, the link between CTCs expressing different integrin subunits, their transcriptional profile and, therefore, their functional activity with respect to metastatic potential remains unclear. Methods Single-cell RNA sequencing of CD45-negative cell fraction of breast cancer patients was performed. All CTCs were divided into nine groups according to their integrin profile. Results СTCs without the gene expression of integrins or with the expression of non-complementary α and β subunits that cannot form heterodimers prevailed. Only about 15% of CTCs expressed integrin subunits which can form heterodimers. The transcriptional profile of CTCs appeared to be associated with the spectrum of expressed integrins. The lowest potential activity was observed in CTCs without integrin expression, while the highest frequency of expression of tumor progression-related genes, namely genes of stemness, epithelial-mesenchymal transition (EMT), invasion, proinflammatory chemokines and cytokines as well as laminin subunits, were observed in CTCs co-expressing ITGA6 and ITGB4. Validation on the protein level revealed that the median of integrin β4+ CTCs was higher in patients with more aggressive molecular subtypes as well as in metastatic breast cancer patients. One can expect that CTCs with ITGA6 and ITGB4 expression will have pronounced metastatic potencies manifesting in expression of EMT and stemness-related genes, as well as potential ability to produce chemokine/proinflammatory cytokines and laminins.